Mineralogical characterization and thermodynamic modelling of scales formed in once through steam generators. (15th January 2022) - Klyukin, Yury I.; Nightingale, Michael; Perdicakis, Basil; Mayer, Bernhard; Tutolo, Benjamin
Graphical abstract: Highlights: Mineral phases in scales are dominated by Na-, Ca-, and Mg- inosilicates. Scales have similar mineralogy regardless of operating conditions/locations. Models replicate composition of condensate phase discharged from steam generator. Models reproduce minerals, constrain thermodynamic and chemical operating parameters. Abstract: Extraction of hydrocarbons from oil sand deposits relies on technologies designed to lower bitumen viscosity, either by thermal energy or combination of thermal energy and solvents. Thermal energy is commonly delivered by steam. Once-through steam generators (OTSGs) are the most common class of generators used to generate steam from boiler feed water (BFW) at high pressure and temperature. Generated steam is used to mobilize the bitumen in the in situ reservoirs, and then water-bitumen emulsion is produced and processed, separating a hydrocarbon product and oil-free water, which subsequently will be reused to generate steam after treatment. Some of the aqueous constituents remaining or added during steam interaction with oil sands and subsequent treatment contribute to scale growth in OTSG tubing. Accumulation of the scale in OTSGs may lead to tubing failure due to overheating. In the present work we focused on inorganic scales – solid phases formed by components dissolved in BFW. We used a suite of geochemical, mineralogical and modelling techniques to characterize and model the inorganic components of scale samples provided by Canada's Oil Sands Innovation Alliance (COSIA) from OTSGs operators at multiple sites in Northeastern Alberta, Canada. We identified the composition of minerals in the scales as Na-, Ca-, and Mg-silicates with relatively low SiO4 4- content (inosilicates). Our modelling results allowed us to constrain the evolution of pressure, temperature, pH, mineral phases, and dissolved components in BFW as it undergoes heating in the OTSG to form steam and boiler-blowdown water. Modelling results are consistent with observed minerals and are promising for future management of scale formation processes.